Answer:
(-1,-5)
Explanation:
So we have the system:
y=3x-2
x-y=4.
We are asked to use substitution. Luckily, it is already setup for this because one of the equations has one of the variables solved for, namely the y=3x-2 equation. We are going to insert y=3x-2 into x-y=4 and solve for x.
x-y=4 (with y=(3x-2) ):
x-(3x-2)=4
Distribute:
x-3x+2=4
Combine like terms:
-2x+2=4
Subtract 2 on both sides:
-2x =2
Divide both sides by -2:
x =-1
Now if y=3x-2 and x=-1, then y=3(-1)-2=-3-2=-5.
So the solution is (-1,-5).